Neden 3 * ln (x) = ln (x ^ 3)?

Neden 3 * ln (x) = ln (x ^ 3)?
Anonim

Cevap:

Logaritma tanımını ve üslerin temel özelliklerini kullanın.

(detaylar aşağıda)

Açıklama:

Temel tanımı:

#color (beyaz) ("XXX") ln (a) b # = anlamına geliyor # E ^ b: #

let #s = 3 ln (x) #

#color (white) ("XXX") rArr ln (x) = s / 3 #

#color (white) ("XXX") rArr e ^ (s / 3) = x #

#color (white) ("XXX") rArr kökü (3) (e ^ s) = x #

#color (white) ("XXX") rArr e ^ s = x ^ 3 #

#color (white) ("XXX") rArrln (x ^ 3) = s #

#color (beyaz) ("XXX") rArrln (x ^ 3) = 3ln (x) #